Carbon Nanotube Yarn: Carbon Nanotube Yarn for Fiber‐Shaped Electrical Sensors, Actuators, and Energy Storage for Smart Systems (Adv. Mater. 5/2020). Issue 5 (4th February 2020) - Jang, Yongwoo; Kim, Sung Min; Spinks, Geoffrey M.; Kim, Seon Jeong
Abstract : In fiber‐based smart systems, carbon nanotube (CNT) fibers and yarns with coil and twist can impose flexible and stretchable properties in addition to excellent electrical and mechanical properties. They can operate as flexible electronic sensors to monitor human health, actuators like artificial muscles, and in energy storage such as energy harvesters and supercapacitors. In article number 1902670, Seon Jeong Kim and co‐workers discuss such progressive advances of CNT yarns, and consider the future challenges in smart electronic systems.